Is there a link between development financial institutions (DFIs) and the economic development? the Malaysian case - Islam, Mohd Aminul (IRJETM, 2015)
The objective of this paper is to examine the existence of relationship between the DFIs and the economic development in Malaysia. We investigated the linkage by applying Autoregressive Distributed Lag (ARDL) method referred as the bounds test approach developed by Pesaran, Shin and Smith in 2001. We have used total assets and the financing activities of DFIs as the variables covering the period 1980 – 2014. Total assets represent the size or development of DFIs while financing activities represent the involvement in promoting economic development. As a proxy for economic development we used real per capita income. We found evidence that both the variables of DFIs in the form of total assets and financing activities have positive and statistically significant long run equilibrium relationship with per capita real income suggesting that the DFIs are important in influencing per capita income in Malaysia.